Effect of vinyl acetate content on the mechanical properties and morphological structures of polypropylene - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2006)
The effect of vinyl acetate (VA) content in ethylene vinyl acetate (EVA) copolymer on the mechanical properties of polypropylene was investigated. Three different EVA copolymers with concentrations of 3 wt%, 6 wt%, 9 wt%, 12 wt% and 15 wt%, were blended to polypropylene. The mechanical properties such as yield and tensile strengths, elastic modulus, Izod impact strength, hardness and melt flow index of the blends were investigated. Relationship between type of vinyl acetate and concentrations, mechanical, MFI and morphological properties were explored.
Keywords: compound; mechanical properties; morphology; BLENDS; COMPOSITES; STRENGTH; BEHAVIOR; EPDM; EVA